Perbandingan Laju Korosi Pada Baja Karbon Rendah dan Stainless Steel Seri 201, 304, dan 430 Dalam Media Nira - Yunaidi Yunaidi (Universitas Janabadra, 2016)
Corrosion can easily be found in various types of equipment made of metallic substrates. Low carbon steel and stainless steels are materials that is widely used in machine tools and structure of the food and beverage industry. Low carbon steel is preferred because it is relatively inexpensive, but less resistant to corrosion, so it is necessary substitution with materials that are more resistant to corrosion, thereby increasing the economic value of equipment or machinery. Juice cane (nira) is the result of a milking cane plant into raw materials for white sugar. Juice contains sucrose, reduction sugar, organic and inorganic substances and water. Juice is acidic as pH below 7 due to the activity of microbes in it, and over time the juice will become more acidic. This study aims to determine the corrosion rate of low carbon steel and stainless steel SS 201, SS 304 and SS 430 series in the medium juice at room temperature. Corrosion testing done in three cell electrodes based on the Tafel extrapolation method. The test results showed that the lowest corrosion rate occurs in SS 304, while the highest corrosion rate occurs in SS 430. The corrosion rate of SS 304 on the juice is low, while the corrosion rate of low carbon steel, SS 201 and SS 430 were moderate. The corrosion rate of the material on the juice is strongly influenced by the juice condition, mainly by the pH value.